Response of tomato varieties (Solanum lycopersicum L.) to water stress (Agro Productividad, 2021)
Background and Objectives: Water scarcity is limiting for tomato (Solanum lycopersicum L) production, due to its sensitive to drought in the different phases of development, so irrigation should be done in an optimal way; because of this, the objective was to evaluate four levels of irrigation in greenhouse tomato varieties.Methods: A completely randomized experimental design with factorial arrangement was used and various agronomic variables, fruit quality and biomass were measured as response variables.Results: Tomatoes were significantly affected (P?0.05) by variety factors (V), irrigation (R), and their interaction. 100% of variety P presented fruits of greater weight (122 g); while weight decreased to 84, 90, 34 and 18 g when reducing water up to 25%, in varieties Cid, P, E and C, respectively. However, in terms of yield and leaf area, 100% of the Cid variety presented the highest values, around 3.3 kg/plant and 8.6 m-2.Conclusions: Variety c was tolerant to water stress and also does not present apical rotting (calcium deficiency) in the fruit.